When Public is Not Enough: A Local Russian Social Movement Between Suppression and Depoliticisation - Turovets, Maria (Javnost-The Public, 2020)
This paper suggests an approach to Russian politics through the theory of depoliticisation. The author suggests that administrative methods of neutralisation and modes of depoliticisation of public discussions are similar in both local and country level of contentious politics. This paper analyses a case of social movement against an extraction project in Russian agricultural region that was approved by the government and initiated by one of the biggest Russian mining companies. The local movement was inspired by the protest movement of 2011–12 and hastened development of local public. Both of the movements faced similar methods of depoliticisation and suppression, but despite the one against extraction was anchored in the local community and protested visible problems, it was divided and mostly dissolved by the end of 2014. Analysis reveals typical tactics of depoliticising conflicts used in controlling political discussion in Russia.